Global Awareness Of Halal Products In Indonesia In Era 4.0 - Naeli Mutmainah; Ahmad Hapidin; Muhammad Ali Ramdhani; Bebeh Wahid Nuryadin; Muharir Muharir; Hisam Ahyani (UIN Siber Syekh Nurjati Cirebon, 2022)
Global awareness of halal products in Indonesia today in the era of 4.0 (disruption) is very important, this is because Indonesia has the opportunity to become the largest sharia economy in the world. One indicator of global awareness of halal products in Indonesia is consumer behavior towards halal products by non-Muslims. This research belongs to the category of library research. The results of the study prove that the potential for attractiveness of Halal food in Indonesia in the era of disruption (4.0) varies, so that in terms of non-Islamic destinations it can be utilized to meet the demand for halal products such as halal food for Muslim tourists, so this needs to be prioritized. This means that halal labeling of halal products in Indonesia is very necessary. As for Global Awareness of Halal Products in Indonesia today, it is a necessity where the level of trust, satisfaction, and intention of recommendations for halal food by the Indonesian people, this can be seen from the general risks that have a significant and positive effect on trust, satisfaction, and intention to recommend halal products to enjoy.